A duration model for the investigation of the adoption spell of improved maize varieties in Ethiopia. (2017) - Lemessa, Sisay Diriba
This paper presents a mixture of descriptive, parametric (Weibull), semi-parametric and non-parametric duration model employed to investigate and analyse the adoption spell of improved maize varieties (IMVs) in Ethiopia. The study based on data gathered from a sample of 898 households. The non-parametric result showed that the speed of adoption of IMVs was expedited in the early years but slugged as the number of years from first awareness increased. The parametric and semi-parametric duration model estimates showed that socio-demographic, social capital and organisational factors curtail the adoption spell of IMVs. Among institutional factors, access to credit and extension contact was found as a significant factor for shortening awaiting time of IMVs adoption. Besides distance from information centres such as market, cooperatives and agricultural extension also significantly determine adoption spell of IMVs. Likewise, input cost, drought stress, pest and diseases have been the main factors that have impede speedy IMVs adoption.